Disposal of milk due to the presence of antibiotic residues in Southern Minas Gerais (Research, Society and Development, 2020)
The presence of antibiotic residues resulting from the treatment of infectious diseases in lactating cows can affect milk quality. Research shows the significant and frequent incidence of residues in milk samples. This incidence causes financial impacts due to milk disposal and the inconvenience that the presence of residues causes in the daily routine of milk processing industries. Therefore, the objective of this work was to verify the volume of milk discarded by the processing industries due to the presence of antibiotic residues in milk collected from properties in the southern region of Minas Gerais, during the year, including dry and rainy seasons, considering β-lactam and tetracycline antibiotic classes. To that end, analyses were performed using the BetaStar® S Combo kit (Neogen) to detect residues of β-lactam and tetracycline classes. Milk was discarded in the industry due to the presence of antibiotic residues of β-lactam and tetracycline classes, and the largest volume of discarded milk was due to the presence of residues of β-lactam class. It was observed that in the spring and summer seasons and in the rainy periods there was an increase in the disposal of milk due to the presence of residues of tetracycline class in relation to the autumn and winter seasons. These results indicate that the misuse of antibiotics in lactating cows and the non-disposal of milk during the grace period in rural properties impact on a greater volume of milk discarded by the industry, causing financial losses.